2014
DOI: 10.3109/09638288.2014.913704
|View full text |Cite
|
Sign up to set email alerts
|

People with lower limb amputation and their sexual functioning and sexual well-being

Abstract: Participants in this study indicated some problems concerning sexual functioning and/or sexual well-being. Some of these problems were of practical nature, and participants would have appreciated some information about how to handle this kind of practical sexual problems. However, such information should not be given at the beginning of the rehabilitation process, as at that time sexuality is not a priority for all patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 27 publications
(29 reference statements)
0
20
0
Order By: Relevance
“…Verschuren and colleagues developed this model through a comprehensive review of the literature as well as their many years of clinical experience. The model has subsequently been used as a guiding theoretical framework in various studies on chronic illness and sexuality [ 12 , 21 , 22 ]. The key assumption of this model is that sexuality is a multifaceted phenomenon, shaped by organic, hormonal, and psychosocial factors, and that chronic illness involves psychosocial stressors in addition to physical symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…Verschuren and colleagues developed this model through a comprehensive review of the literature as well as their many years of clinical experience. The model has subsequently been used as a guiding theoretical framework in various studies on chronic illness and sexuality [ 12 , 21 , 22 ]. The key assumption of this model is that sexuality is a multifaceted phenomenon, shaped by organic, hormonal, and psychosocial factors, and that chronic illness involves psychosocial stressors in addition to physical symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…The users state that it is important for themselves as well as for their partners or others in their surroundings to accept the prosthetic device [ 54 , 79 , 82 , 85 87 ]. The acceptance of the device is related to the need for sexual activity or proper sexual functioning [ 70 , 83 , 100 , 103 , 104 ], predominantly reported by male users, because body image disturbances [ 1 ] and self-consciousness can lead to sexual dysfunction [ 103 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, to incorporate sexuality into post-amputation rehabilitation goals, rehabilitation care providers must address sexuality with their patients. In a qualitative study of individuals with recent LEA, it was noted that most study participants agreed that discussing sexuality with their care providers would have been useful (Verschuren, Geertzen, Enzlin, Dijkstra, & Dekker, 2015). Even some partners of those with recent LEA indicated that discussing sexuality with a professional might be helpful (Verschuren, Zhdanova, et al, 2013), although patient (and partner) anxiety may prevent them from initiating a discussion (Gianotten, Bender, Post, & Höing, 2006).…”
Section: Discussionmentioning
confidence: 99%